1996
DOI: 10.1002/(sici)1097-461x(1996)60:1<381::aid-qua37>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the low-lying electronic states of phenanthrene: Exact PPP results

Abstract: mWe report properties of the exact low-lying states of phenanthrene, its anion and dianion within the Pariser-Parr-Pople (PPP) model. The experimentally known singlet states of the neutral molecule are well reproduced by the model. The intensities for one and two photon absorption to various singlet states are also in good agreement with experiment. From the bond orders of these states, we predict the equilibrium geometries. The relaxation energies of these states, computed from charge-charge correlations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…[28][29][30][31][32] Whereas trans-stilbene photoisomerizes to cis-stilbene, the reverse isomerization reaction competes with electrocyclization of cis-stilbene to 4a,4b-dihydrophenanthrene, which irreversibly oxidizes to phenanthrene. 25 Numerous excited-state calculations at various levels of theory have been reported for trans-stilbene, 26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] cis-stilbene, 26,38,39,[41][42][43][44][45][46][47]49,50 and phenanthrene, [51][52][53] with some of the most comprehensive work by Merchan and coworkers using CASPT2 (complete active space self-consistent field with second-order perturbative correction). 48,50,53 However, there have been only a limited number of studies on the 2PA properties, and the reported cross sections vary by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Whereas trans-stilbene photoisomerizes to cis-stilbene, the reverse isomerization reaction competes with electrocyclization of cis-stilbene to 4a,4b-dihydrophenanthrene, which irreversibly oxidizes to phenanthrene. 25 Numerous excited-state calculations at various levels of theory have been reported for trans-stilbene, 26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] cis-stilbene, 26,38,39,[41][42][43][44][45][46][47]49,50 and phenanthrene, [51][52][53] with some of the most comprehensive work by Merchan and coworkers using CASPT2 (complete active space self-consistent field with second-order perturbative correction). 48,50,53 However, there have been only a limited number of studies on the 2PA properties, and the reported cross sections vary by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Phenanthrene like azulene has no center of symmetry. Possible resonance structures of phenanthrene have been discussed by Chakrabarti et al 137 The classification of biphenylene has been intensively discussed. 123,[138][139][140][141][142] Depending on how the electrons are counted, either as two benzene molecules with 6π electrons or collectively as 12π electrons, which equals 4n with n ) 3, biphenylene should be considered as an aromatic or as an antiaromatic molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Phenanthrene like azulene has no center of symmetry. Possible resonance structures of phenanthrene have been discussed by Chakrabarti et al The classification of biphenylene has been intensively discussed. , Depending on how the electrons are counted, either as two benzene molecules with 6π electrons or collectively as 12π electrons, which equals 4 n with n = 3, biphenylene should be considered as an aromatic or as an antiaromatic molecule. In the work of Beck et al it was argued that the length of the bonds between the two ring systems is large enough to ensure that there is no interaction between the two ring systems and that biphenylene can be regarded as an aromatic molecule.…”
Section: Introductionmentioning
confidence: 99%